2000
DOI: 10.1088/0954-3899/26/8/307
|View full text |Cite
|
Sign up to set email alerts
|

Restoration and breakdown of the ϕ→-ϕ symmetry in the (1+1)-dimensional massive sine-Gordon field theory by quantum and finite-temperature effects

Abstract: Within the framework of the Gaussian wave-functional approach, we investigate the influences of quantum and finite-temperature effects on the Z2-symmetry(φ → −φ) of the (1+1)-dimensional massive sine-Gordon field theory. It is explicitly demonstrated that by quantum effects the Z2symmetry can be restored in one region of the parameter space and dynamically spontaneously broken in another region. Moreover, a finite-temperature effect can further restore the Z2-symmetry only.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…On the other hand, we have explicitly shown that, in the case of (1 + 1) dimensional λψ 4 (which is non-integrable), it is not possible to solve in general the recurrence relation establishing the non-linear to linear mapping, except for a restricted class of solutions for f . Other interesting aspects of the sine-Gordon model for which the present approach could be useful are the finite temperature behavior [70] and the duality with the Thirring model both at zero [36] and finite temperature [71].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we have explicitly shown that, in the case of (1 + 1) dimensional λψ 4 (which is non-integrable), it is not possible to solve in general the recurrence relation establishing the non-linear to linear mapping, except for a restricted class of solutions for f . Other interesting aspects of the sine-Gordon model for which the present approach could be useful are the finite temperature behavior [70] and the duality with the Thirring model both at zero [36] and finite temperature [71].…”
Section: Discussionmentioning
confidence: 99%